Mosque for All, Socio-Spatial Inclusion in Mosque Architecture: The Case of Türkiye - Gün, Ahmet (Journal of Islamic Architecture, 2025)
Today, the design and management of the mosque are subject to criticism in many ways, like not being responsive to the needs of different user groups and causing socio-spatial justice problems between genders and generations. This study examines the extent to which mosques provide socio-spatial inclusion by analyzing problems experienced in mosques, user satisfaction, and user perceptions of the socio-spatial inclusiveness of mosques. Methodologically, an online survey was conducted with 521 participants living in Türkiye. In addition, a workshop will be held with 17 participants who are currently involved in research on mosque design to develop proposals at a strategic level to address the identified issues. This study reveals that there are critical socio-spatial problems faced by users in mosques: (1) problems of representation inequality in decision-making about the design and management of mosques (the gaps of representation equality), (2) limited responsiveness to users' spatial expectations due to the neglect of the needs of important stakeholders such as women, children and youth in society (3). Only a very limited group of users (18.4%) are satisfied with the spatial experience in mosques. Additionally, almost one-third of the respondents (30.1%) perceive mosques as 'middle-aged or elderly male-dedicated spaces,' with this perception being more prevalent among women and young people. At the end of the study, we discuss the socio-spatial dimensions that will form the basis for a “Mosque for All”.